Impact of celastrol on mitochondrial dynamics and proliferation in glioblastoma - Lei Liang; Wenying Lv; Gang Cheng; Mou Gao; Junzhao Sun; Ning Liu; Hanbo Zhang; Baorui Guo; Jiayu Liu; Yanteng Li; Shengqiang Xie; Jiangting Wang; et al. (BMC Cancer)
Abstract Background Targeting mitochondrial dynamics offers promising strategies for treating glioblastoma multiforme. Celastrol has demonstrated therapeutic effects on various cancers, but its impact on mitochondrial dynamics in glioblastoma multiforme remains largely unknown. We studied the effects of Celastrol on mitochondrial dynamics, redox homeostasis, and the proliferation. Methods Mito-Tracker Green staining was conducted on U251, LN229, and U87-MG cells to evaluate the effects of Celastrol on mitochondrial dynamics. The Western blot analysis quantified the expression levels of mitochondrial dynamin, antioxidant enzymes, and cell cycle-related proteins. JC-1 staining was performed to discern mitochondrial membrane potential. Mitochondrial reactive oxygen species were identified using MitoSOX. The proliferative capacity of cells was assessed using Cell Counting Kit-8 analysis, and colony formation assays. Survival analysis was employed to evaluate the therapeutic efficacy of Celastrol in C57BL/6J mice with glioblastoma. Results Our findings suggest that Celastrol (1 and 1.5 µM) promotes mitochondrial fission by downregulating the expression of mitofusin-1. A decrease in mitochondrial membrane potential at 1 and 1.5 µM indicates that Celastrol impaired mitochondrial function. Concurrently, an increase in mitochondrial reactive oxygen species and impaired upregulation of antioxidant enzymes were noted at 1.5 µM, indicating that Celastrol led to an imbalance in mitochondrial redox homeostasis. At both 1 and 1.5 µM, cell proliferation was inhibited, which may be related to the decreased expression levels of Cyclin-dependent kinase 1 and Cyclin B1. Celastrol extended the survival of GBM-afflicted mice. Conclusion Celastrol promotes mitochondrial fission in glioblastoma multiforme cells by reducing mitofusin-1 expression, accompanying mitochondrial dysfunction, lower mitochondrial membrane potential, heightened oxidative stress, and decreased Cyclin-dependent kinase 1 and Cyclin B1 levels. This indicates that Celastrol possesses potential for repurposing as an agent targeting mitochondrial dynamics in glioblastoma multiforme, warranting further investigation.